Determinants of Generation Z’s Purchase Decisions for Viral Foods Online Fear of Missing Out as a Mediating Variable - Mayabubun, Khoirunisa Fadia Nadayu; Hidayat, Anas (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The phenomenon of viral foods spreading through social media has transformed Generation Z’s purchasing decision-making patterns; however, the psychological mechanisms that mediate the impact of the digital environment on purchasing decisions still require further study. This study aims to analyze the influence of social media exposure, electronic word of mouth (E-WOM), and social influence on viral food purchasing decisions, with Fear of Missing Out (FoMO) as a mediating variable among Generation Z in Jayapura City. The study employs a quantitative approach using a survey design with 200 respondents selected via purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4. The results indicate that social influence has a positive and significant effect on purchasing decisions, both directly and through FoMO. Additionally, E-WOM has a positive and significant effect on FoMO and indirectly influences purchasing decisions through FoMO. Conversely, social media exposure does not have a significant effect on either FoMO or purchasing decisions; therefore, FoMO does not mediate this relationship. These findings suggest that Generation Z’s purchasing decisions regarding viral food items are more influenced by social and psychological factors than by direct social media exposure. Consequently, marketing strategies based on social interaction and the creation of FoMO have the potential to be more effective in driving purchasing decisions.